PWE-082 'hot gall bladders' – time to innovate?. (22nd June 2015) - Goussous, G; Spence, J; Evans, R; Iqbal, F; Brook, A; Rotundo, A; Rao, V
Abstract : Introduction: Emergency admissions with gall bladder related symptoms account for significant component of acute surgical take in every busy surgical unit. There appears to be three subgroups of patients by way of presentation with implications towards appropriate management. Based on intra operative findings, an alternative model of management is proposed with implications towards potential savings in terms of inpatient stay. Method: A prospective study of all consecutive acute admissions with gall bladder symptoms in a busy tertiary unit over a six month period was undertaken. Demographic data along with mode of presentation, inflammatory markers and intra operative findings were analysed. Differences in inflammatory markers between different subgroups were analysed using one way ANOVA. Total number of inpatient days were calculated and potential savings in terms of in patient days after applying the proposed new model of management was assessed. Results: 145 patients (Age: 50; range:16–85, M:F = 44:101) were admitted with symptoms suggestive of gall bladder pathology over a six month period. Based on intra operative findings, three distinct groups of patients were recognised: biliary colic with thin walled gall bladder (n = 51), acute cholecystitis with thick walled inflamed gall bladder (n = 78) and complicated cholecystitis with empyema or localised perforation (n = 16). Excluding the patients with pancreatitis, there was significant difference in mean CRP levels between the three groups (biliary colic: 21.9, 95% confidence interval [CI] 9.0–34.8; acute cholecystitis: 85.1, 95% CI 58.4–111.7; complicated cholecystitis: 181.4, 95% CI 96.8–265.9, p = 0.000). There was also significant difference in mean WCC levels (biliary colic: 9.4, 95% CI 8.0–10.8; acute cholecystitis: 11.7, 95% CI 10.5–12.8; complicated cholecystitis: 13.9, 95% CI 11.8–16.0, p = 0.002). There was no difference in number of inpatient days and post op complications between the groups. The median length of stay was 7 (1–27) with the interval between admission and surgery being 4(1–15). There was no difference in number of inpatient days between the three subgroups. If the patients who had biliary colic and acute cholecystitis without pancreatitis were managed on an outpatient basis with deferred surgery on a day case basis, a saving of 594 inpatient days could be done with potential for significant savings for the NHS. Conclusion: We suggest that those with biliary colic and acute cholecystitis can be managed on an out patient basis and have their surgery done on a day case basis within a reasonable time frame thereby saving a significant number of inpatient days. This has significant implications especially in times of increasing bed pressures in the NHS. Disclosure of interest: None Declared.